2021
DOI: 10.3389/fenvs.2021.700768
|View full text |Cite
|
Sign up to set email alerts
|

Appraisal of Carbon Capture, Storage, and Utilization Through Fruit Crops

Abstract: Nowadays, rapid increases in anthropogenic activities have resulted in increased greenhouse gases (GHGs; CO2, CH4, N2O) release in the atmosphere, resulting in increased global mean temperature, aberrant precipitation patterns, and several other climate changes that affect ecological and human lives on this planet. This article reviews the adaptation and mitigation of climate change by assessing carbon capture, storage, and utilization by fruit crops. Perennial plants in forests, fruit orchards, and grasslands… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 85 publications
0
5
0
Order By: Relevance
“…To avoid losses in fruit production due to e-CO2, Haokip et al (2020) proposed implementing a plan based on a strategic scientific impact assessment with the adaptations and mitigation necessary. Sharma et al (2021) confirmed that sustainable fruit production systems could mitigate emissions and sequester carbon within the atmosphere. Besides the shallow soil tillage, which preserves the soil organic matter, the structural characteristics of orchards and vineyards, including their long-life cycle, permanent organs (trunk, branches, roots), and high yields, force them to accumulate a considerable amount of carbon (Sharma et al, 2021).…”
Section: Aspects Of Mitigating the Adverse Effect Of Co2 On Fruit Treesmentioning
confidence: 71%
See 1 more Smart Citation
“…To avoid losses in fruit production due to e-CO2, Haokip et al (2020) proposed implementing a plan based on a strategic scientific impact assessment with the adaptations and mitigation necessary. Sharma et al (2021) confirmed that sustainable fruit production systems could mitigate emissions and sequester carbon within the atmosphere. Besides the shallow soil tillage, which preserves the soil organic matter, the structural characteristics of orchards and vineyards, including their long-life cycle, permanent organs (trunk, branches, roots), and high yields, force them to accumulate a considerable amount of carbon (Sharma et al, 2021).…”
Section: Aspects Of Mitigating the Adverse Effect Of Co2 On Fruit Treesmentioning
confidence: 71%
“…Sharma et al (2021) confirmed that sustainable fruit production systems could mitigate emissions and sequester carbon within the atmosphere. Besides the shallow soil tillage, which preserves the soil organic matter, the structural characteristics of orchards and vineyards, including their long-life cycle, permanent organs (trunk, branches, roots), and high yields, force them to accumulate a considerable amount of carbon (Sharma et al, 2021). Also, Marín et al (2016) reported high carbon fixation rates (17.7 t year -1 ) in agroforestry systems with citrus species.…”
Section: Aspects Of Mitigating the Adverse Effect Of Co2 On Fruit Treesmentioning
confidence: 71%
“…The carbon sequestration of 20 mg/ha/year in above-ground parts and 35.6 mg/ha/year in below-ground parts were sunk by Phyllostachys heteroclada in China forest (Wang et al 2013). The carbon assimilation of 24.7 mg/ha/year in aboveground parts and 69.2 mg/ha/year in below-ground parts and 42.2 mg/ha/year in above-ground parts and 59.0 mg/ ha/year in below-ground parts were sunk by the Phyllostachys maikinoi and Phyllostachys meyeri in Taiwan and China forest respectively (Sharma et al 2021). The carbon assimilation of 14.5 mg/ha/year in above-ground parts and 12.2 mg/ha/year in below-ground parts and 28.2 mg/ ha/year in above-ground parts and 15.1 mg/ha/year in below-ground parts were sunk by the Phyllostachys nidularia and Phyllostachys nigra in South Korea and China forest respectively (Lv et al 2020).…”
Section: Other Bamboo Speciesmentioning
confidence: 97%
“…Fruit trees have excellent structural qualities that enable them to acquire a substantial quantity of carbon, such as a long life cycle, permanent organs like trunks, branches, and roots, zero soil tillage (maintaining soil organic matter), and high quality and yield. Consequently, fruit plants have great potential to absorb atmospheric carbon [96]. Global warming and air pollution are two challenges the globe faces today, and the two problems are interrelated.…”
Section: Variation In Socp and Mec Of Study Areamentioning
confidence: 99%